APLIKASI ON-DEMAND SERVICE PEDAGANG KELILING BERBASIS ANDROID - Asep Hidayat, - (2019)
The problem experienced by traveling salesman is not knowing the position of the buyer. When traveling salesman move, the place is sometimes quiet with buyers. In recent years, on-demand mobile service applications have begun to develop. To overcome the problems faced by traveling salesman, in this study a mobile on-demand service system was created. There are several concepts of on-demand service that must be implemented in the system, namely the system must be able to fulfill user requests quickly, the system must sell products that are clear and controlled, the system must be able to connect customers with service providers, requests must be collected using the application and served offline , and service providers can decide when to work. Based on the results of usability analysts using use questionnaires, most of the correspondents have a positive response that this application is a useful application. Then for the convenience of using the application, all respondents answered with a positive response. For the technology used there are several differences between the technologies applied by on-demand mobile traveling salesman and other on-demand service systems. For the server section, the on-demand service for mobile merchants still uses monolith architecture while Go-Food uses the microservice architecture. To process data in realtime, the traveling salesman system uses Firebase Cloud Firestore technology, while for Go-Food uses data stream technology and uses the Kafka platform. For map technology, both systems use the Google Maps API. For mobile technology, the GO-FOOD application uses the RxJava library. Keywords: traveling salesman, On Demand Mobile Service, use questionnare